A health information platform for Case Managed Neglected Tropical Diseases - A case study from Mozambique - de Kruijff, Arie (Graduate School of Business (GSB), 2021)
Leprosy, as one of the neglected tropical diseases, is an ancient disease that requires a slow and patient approach for its diagnosis and treatment involving various actors along the way. This care system has traditionally been supported by a paper based health information system still in use today in many endemic countries. In Mozambique, various attempts at modernizing the system have failed. The continued transmission of the disease is again highlighting the need for sharper strategic approaches supported by detailed information and better coordination between the various care actors in the system. This study coincided with the design and implementation of a new health information system for the case managed neglected tropical diseases (NTD) care sector in Mozambique. A Soft Systems Methodology (Action Research) approach was followed during this implementation process in an attempt to incorporate the perspectives of various actors and many institutional relationships that have an impact on the outcomes of this complex disease. The aim of the study was not only to identify factors that would contribute to the successful introduction of the health information system, but also to contribute to better knowledge management within this specific NTD care context. The study utilized group work, rich picture creation and individual interviews to build conceptual models for knowledge management in this context. It also tried to ground this by analyzing lessons from previous unsuccessful NTD information systems as well as the experiences from other countries in Africa where a similar infrastructure was implemented successfully.